Liquid refractometer based mirrorless fiber optic displacement sensor - Krishnan, G. (Elsevier B.V., 2016)
Liquid refractometer based mirrorless fiber optic displacement sensor is proposed and demonstrated. Various liquid samples with refractive index in the range of 1.333-1.433 RIU were used as modulator. The refractometer sensor was operated based on intensity modulation with regard to displacement sensor. Each of the tested samples has its own fingerprint. This allows the performance of the sensor to be quantified based on the front slope, back slope and peak voltage. The peak voltage is optimized at constant displacement of 3 mm. The sensitivity of the refractometer sensor based mirrorless fiber optic displacement sensor is achieved as 188.37 mV/mm/RIU with repeatability of 99.87 and resolution of 0.00531RIU. The sensor work based on the peak voltage. The higher the peak voltage means the higher the refractive index of the liquid medium. The collection of more lights entering into the receiver is realized due to the contribution from the reflectivity of the surface liquid. Such mirrorless liquid refractometer sensor offering many advantages including the simplicity, easier, faster and cheaper compared to conventional refractometer. Â© 2016 Elsevier B.V. All rights reserved.